Main pests and diseases of cotton in sub-Saharan Africa - Vaissayre, M.; Cauquil, J. (CIRAD / CTA, 2000)
This illustrated pocket guide is intended for cotton growers who need to identify common pests and diseases rapidly in the field. The pests and diseases are grouped in order of their occurrence in the cotton development cycle and include seedling and leaf pests, sucking insects, mites and bollworms.